Qaḍiyyatul Waṭān fī Dīwāni “at-Tajawwāl fī al-Mawāni-i al-Ba’īdah” li ‘Ārif Khuḍairī wa Dīwāni “Damai dalam Sentuhan” li Syukrī Zain (Dirāsah Tahlīliyyah Muqāranah) - Rahmah Bt Ahmad H. Osman; Rafidah Bt Haji Abdullah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2017)
AbstractThis article tries to compare the issue of homeland in these two collection of poems entitled “at-tajawwal fī al-mawāni-i al-ba’īdah” by the Egyptian poet ‘Arif Khudairiy and “Damai dalam Sentuhan” by Syukri Zeyn from Brunei Darussalam. Those two poets chosen for comparative study in this research, because their impressions such as the extensive cultural experience of ‘Arif Khudairiy in the Malay countries as Brunei Darussalam and Malaysia, that we will see how Malay environment affected his poetic work. For the Syukri Zeyn as the pioneer of modern Islamic poetry in Brunei Darussalam he has Arabic language culture as he graduated from Al-Azhar University. However, the important reason is a close relationship between those two poets. In this comparison, we have relied on comparative descriptive analytical methodology. The methodology covers clarifying the issue of homeland in Arabic and Malay poetry, describing the information about those two poets and their collection of poems and analyzing the issue of homeland according to the poets followed by highlighting the similarities and differences in their discussion of the issue of homeland. The result is that there are similarities between the poets in several aspects, such as: the ease of language used, the use of symbols and rhetorical images and some locations where the poets wrote their poems. Then, the differences which can be seen in those two poets are the purpose of poems, the language fluency, and the number of stanzas and lines of poems.Keywords: The issue, Homeland, Poems, The Lines of Poem, Comparative. قضية الوطن في ديوان "التجوال في الموانئ البعيدة" لعارف خضيريوديوان "دامي دالم سنتوهن" لشكري زين(دراسة تحليلية مقارنة) بقلم: رحمة بنت أحمد الحاج عثمانالجامعة اﻹسلامية العالمية ماليزياrahmahao@iium.edu.myورفيدة بنت الحاج عبد اللهالجامعة السلطان الشريف علي برونايمُلخَّص تُقارن المقالة بين قضية الوطن في الديوانين؛ ديوان "التجوال في الموانئ البعيدة" للشاعر المصري عارف خضيري، وديوان "دامي دالم سنتوهن" للشاعر الملايوي البروناوي شكري زين, وقد اخترا الشاعرين لدراستهما دراسة مقارنة لأن لعارف خضيري خبرة ثقافية واسعة في بلاد الملايو من مثل بروناي دار السلام وماليزيا، لذا سنرى مدى تأثره بالبيئة الملايوية في عمله الشعري, أما شكري زين فيُعدُّ رائد الشعر الإسلامي الحديث في بروناي دار السلام، وله ثقافة لغوية عربية إذ تخرج من جامعة الأزهر, ومن ثم هناك علاقة وثيقة بين الشاعرين المذكورين, وقد اعتمدنا في هذه المقارنة على المنهج الوصفي التحليلي المقارن، ففي البداية توضيح قضية الوطن في الشعر العربي والملايوي، ثم التعريف بالشاعرين وديوانيهما, ثم تحليل قضية الوطن عند الشاعرين، وإبراز التشابه والاختلاف في مناقشتهما قضية الوطن, والنتيجة أن التشابه بين الشاعرين في عدة أمور, منها: سهولة اللغة المستخدمة، واستخدام الرموز والصور البلاغية، وبعض الأماكن التي كتب فيها الشاعران قصائدهما, أما الاختلاف فنراه في أغراض القصائد، واستخدام اللغة الفصيحة، وعدد المقاطع والسطور القصائد.الكلمة الرئيسية: القضية، الوطن، الشعر، القصيدة، المقارنة.